Association of interleukin-6 with suicidal ideation in veterans: a longitudinal perspective - Sun, Shengnan; Wilson, Caroline M.; Alter, Sharon; Ge, Yongchao; Hazlett, Erin A.; Goodman, Marianne; Yehuda, Rachel; Galfalvy, Hanga; Haghighi, Fatemeh (Frontiers in Psychiatry, 2023)
Studies showing associations between inflammation in suicide are typically crosssectional. Present study investigated how cytokine levels track with suicidal ideation and severity longitudinally. Methods: Veterans with a diagnosis of Major Depressive Disorder (MDD) with or without suicide attempt history (MDD/SA n=38, MDD/NS n=41) and non-psychiatric non-attempter controls (HC n=33) were recruited, MDD/SA and HC groups were followed longitudinally at 3-and 6 months. Blood plasma was collected and processed using Luminex Immunology Multiplex technology. Results: Significant differences in depression severity (BDI) and suicidal ideation severity (SSI) were observed across all groups at study entry, wherein MDD/SA group had the highest scores followed by MDD/NS and HC respectively. Cytokines IL-1β, IL-4, TNF-α, IFN-γ, and IL-6 were examined at study entry and longitudinally, with IL6 levels differing significantly across the groups (p=0.0123) at study entry. Significant differences in changes in cytokine levels between depressed attempters and the control group were detected for IL-6 (interaction F1, 91.77 =5.58, p=0.0203) and TNF-α (F 1,101.73 =4.69, p=0.0327). However, only depressed attempters showed a significant change, in IL-6 and TNF-α levels, decreasing over time (IL-6: b=-0.04, 95%CI= (-0.08, -0.01), p=0.0245 and TNF-α: b=-0.02, 95%CI= (-0.04, -0.01), p=0.0196). Although IL-6 levels were not predictive of suicidal ideation presence (OR=1.34, 95% CI= (0.77, 2.33), p=0.3067), IL-6 levels were significantly associated with suicidal ideation severity (b=0.19, p=0.0422). Discussion: IL-6 was not associated with presence of suicidal ideation. IL-6 however, was associated with severity of ideation, suggesting that IL-6 may be useful in clinical practice, as an objective marker of heightened suicide risk.